Optical absorption in core-shell quantum antidot under applied co-directed electric and magnetic fields. - Holovatsky, Volodymyr; Chubrei, Maryna (Taylor & Francis Group, 2022)
Using the matrix diagonalization method within the effective mass approximation and the rectangular potential profile, we investigate optical absorption coefficients (OAC) in the core-shell quantum anti- dot (QAD) Al0.3Ga0.7As/GaAs/Al0.3Ga0.7As in the presence of applied co-directed electrical and magnetic fields. The electric field effect on the electron wave functions, energy spectrum, oscillator strength of the intersubband electronic transitions is calculated for different size of QAD core and different value of the magnetic field induction. The total, linear and nonlinear optical absorption coefficients in QAD are obtained by considering 1 s-1p and 1p-1d electron quantum transi- tions as functions of the incident photon energy.
Keywords: density distribution; energy spectrum; intersubband transition; optical absorption coefficient; quantum antidot